Layer up! : the ultimate glow-up guide for cakes - Gampp, Yolanda (How To Cake It Books, an imprint of Kayppin Media, 2022)
"Layer it on. Layer it in. Level it up! In her newest book, beloved celebrity cake master Yolanda Gampp teaches you how to level UP your cakes by layering IN explosive flavors and delicious desserts. In this ultimate glow-up guide for cakes, How to Cake It and Crime Scene Kitchen star Yolanda Gampp plays with flavor profiles and shares twenty-one 'stuffed-cake' recipes (plus seventy-two delicious stand-alone desserts, toppings, and buttercreams) to help you level up your cake game and prove that it really is what's inside that counts. Talk About a Surprise Inside. Sprinkles spilling out of cakes? That's great but your fave ooey gooey desserts, bursting out of cakes? Yes!! You can expect an explosion of flavor (and actual desserts!) in every stuffed-cake recipe thoughtfully developed and rigorously tested by Yo herself. Layers on Layers of Flavor. Modern caking is all about layering! Each stuffed, 'dessert-inside' cake recipe will also include recipes for other stand-alone desserts, such as key lime pie or cheesecake, that get sandwiched between or placed on top of delicious classic cake layers. Stylish Cakes, Flavor First. The outside of these mouth-watering, fondant-free layered cakes are aesthetically aspirational and insta-worthy; however, the primary focus of these recipes is indulgent flavor profiles. Big on Baking, Short on Time? Don't have time to make a layered cake? No problem! The stand-alone dessert and cake recipes included in each stuffed cake recipe can be used on their own." --